High Altitude Pregnancies and Vascular Dysfunction: Observations From Latin American Studies - Gonzalez-Candia, Alejandro; Herrera, Emilio A. (Frontiers in Physiology, 2021)
An estimated human population of 170 million inhabit at high-altitude (HA, above 2500m). The potential pathological effects of HA hypobaric hypoxia during gestation have been the focus of several researchers around the world. The studies based on the Himalayan and Central/South American mountains are particularly interesting as these areas account for nearly 70% of the HA world population. At present, studies in human and animal models revealed important alterations in fetal development and growth at HA. Moreover, vascular responses to chronic hypobaria in the pregnant mother and her fetus may induce marked cardiovascular impairments during pregnancy or in the neonatal period. In addition, recent studies have shown potential long-lasting postnatal effects that may increase cardiovascular risk in individuals gestated under chronic hypobaria. Hence, the maternal and fetal adaptive responses to hypoxia, influenced by HA ancestry, are vital for a better developmental and cardiovascular outcome of the offspring. This mini-review exposes and discusses the main determinants of vascular dysfunction due to developmental hypoxia at HA, such as the Andean Mountains, at the maternal and fetal/neonatal levels. Although significant advances have been made from Latin American studies, this area still needs further investigations to reveal the mechanisms involved in vascular dysfunction, to estimate complications of pregnancy and postnatal life adequately, and most importantly, to determine potential treatments to prevent or treat the pathological effects of being developed under chronic hypobaric hypoxia.